PENGUKURAN KANDUNGAN AIR TANAH PADA PERTANAMAN JARAK PAGAR (JATROPHA CURCAS L.) SOIL WATER CONTENT MEASUREMENT UNDER JATROPHA CROP (JATROPHA CURCAS L.) - Gusti Rusmayadi; Bregas Budianto (Agromet, 2009)
Management strategies development for efficient water utilization of crop production requires sensitive measurements of changes in soil water content on a dynamic basis. Many of the methods currently used for measuring these changes are destructive, slow, or relatively expensive for large-scale investigations. A sensor that low-cost, nondestructive soil moisture sensor for measuring changes in soil volumetric water content on the basis of changes in the dielectric constant of the soil water were available. So, this research was carried out to quantify soil water content on Jatropha under rainfall condition, four levels of nitrogen fertilizer (N) and two population densities (P). The experiments used a systematic Nelder fan design with 9 spokes and 4 rings were conducted at SEAMEO-BIOTROP field experiment in 2007. Based on evaluation this instrument can use to measurement soil water content in various environment.